2018
DOI: 10.1177/0363546518785901
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Injury Risk After Sport-Related Concussion: A Systematic Review and Meta-analysis

Abstract: Based on the evidence of higher risk of MSK injuries after concussion, standard clinical assessments for athletes with concussion should include not only physical symptoms and cognitive function before return to sport but also neuromuscular risk factors associated with increased risk for MSK injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
144
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(149 citation statements)
references
References 44 publications
(107 reference statements)
3
144
2
Order By: Relevance
“…The presence of these sensorimotor deficits in individuals whose injury occurred <2 years ago (despite "clinical recovery") may help explain the growing body of evidence demonstrating that athletes with a recent history of concussion are at a greater risk of sustaining further concussive 3 and lower-limb musculoskeletal injuries. 4 Furthermore, the use of inertial sensor technology may help address some of the limitations of the traditional clinical assessments which have shown no utility in identifying those at an increased risk of musculoskeletal injury post-concussion. 34 For example, recent prospective research by Johnston et al 15 reported that Rugby Union players with poorer dynamic balance performance measured using inertial sensor technology during the YBT were at a three times greater relative-risk of concussion than individuals with optimal performance.…”
Section: F I G U R E 2 Violin Plots Illustratingmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of these sensorimotor deficits in individuals whose injury occurred <2 years ago (despite "clinical recovery") may help explain the growing body of evidence demonstrating that athletes with a recent history of concussion are at a greater risk of sustaining further concussive 3 and lower-limb musculoskeletal injuries. 4 Furthermore, the use of inertial sensor technology may help address some of the limitations of the traditional clinical assessments which have shown no utility in identifying those at an increased risk of musculoskeletal injury post-concussion. 34 For example, recent prospective research by Johnston et al 15 reported that Rugby Union players with poorer dynamic balance performance measured using inertial sensor technology during the YBT were at a three times greater relative-risk of concussion than individuals with optimal performance.…”
Section: F I G U R E 2 Violin Plots Illustratingmentioning
confidence: 99%
“…Specifically, athletes with a history of a concussive injury have an increased risk of sustaining future concussive 3 and/or lower-limb musculoskeletal injuries. 4 While the underlying mechanism behind this relationship has yet to be fully uncovered, it has been suggested that the association may be related to the presence of subtle sub-clinical sensorimotor and neurocognitive deficits which persist beyond the resolution of the traditional signs and symptoms of concussion. 5 These concerns are beginning to be substantiated, with research demonstrating that sensorimotor control deficits post-clinical recovery from concussion may be more pronounced during dynamic balance 6 and dual-task situations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The female athlete triad (bone density abnormalities, menstrual dysfunction, and abnormal nutrition status) is present in 40% of high school female athletes, 69% of female endurance athletes, and 77% of female ballet dancers . Women also carry a 56% to 265% increased risk of concussion compared to their male counterparts . These diagnoses can all be managed by musculoskeletal physiatrists.…”
Section: Introductionmentioning
confidence: 99%
“…18 Women also carry a 56% to 265% increased risk of concussion compared to their male counterparts. 6,19 These diagnoses can all be managed by musculoskeletal physiatrists. Furthermore, many, if not all can be well managed with first-line conservative treatment including medications and physical therapy, which are routinely prescribed by physiatrists.…”
Section: Introductionmentioning
confidence: 99%